2016
DOI: 10.1093/cercor/bhv342
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning Induces Persistent Attentional Capture by Nonsalient Shapes

Abstract: Visual attention can be attracted automatically by salient simple features, but whether and how nonsalient complex stimuli such as shapes may capture attention in humans remains unclear. Here, we present strong electrophysiological evidence that a nonsalient shape presented among similar shapes can provoke a robust and persistent capture of attention as a consequence of extensive training in visual search (VS) for that shape. Strikingly, this attentional capture that followed perceptual learning (PL) was evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 66 publications
11
57
0
1
Order By: Relevance
“…However, the filtering of task-irrelevant stimuli may occur at different stages of processing, and may involve different mechanisms. Recently, it has been shown that the mechanisms subserving attentional orienting are subject to profound and enduring plastic changes based on previous experience (Kelley & Yantis, 2009;Qu, Hillyard, & Ding, 2016), and that habituation can selectively impact attentional processes (Turatto & Pascucci, 2016). Therefore, the perceptual and semantic processing of taskirrelevant stimuli might occur independently of attentive processes 1988;Elliott & Cowan;Gronau, Cohen, & Ben-Shakhar, 2009;Öhman, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…However, the filtering of task-irrelevant stimuli may occur at different stages of processing, and may involve different mechanisms. Recently, it has been shown that the mechanisms subserving attentional orienting are subject to profound and enduring plastic changes based on previous experience (Kelley & Yantis, 2009;Qu, Hillyard, & Ding, 2016), and that habituation can selectively impact attentional processes (Turatto & Pascucci, 2016). Therefore, the perceptual and semantic processing of taskirrelevant stimuli might occur independently of attentive processes 1988;Elliott & Cowan;Gronau, Cohen, & Ben-Shakhar, 2009;Öhman, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Without any explicit reward feedback, simply locating a target repeatedly over trials can give rise to attentional biases that mirror value-driven attention (e.g., Kyllingsbaek, Schneider, & Bundesen, 2001; Kyllingsbaek, Van Lommel, Sorensen, & Bundesen, 2014; Qu, Hillyard, & Ding, in press; Shiffrin & Schneider, 1977). It was traditionally thought that such selection history biases require substantial training to develop, typically thousands of trials over multiple days (Kyllingsbaek et al, 2001, 2014; Shiffrin & Schneider, 1977).…”
Section: Does the Presence Of Reward During Training Actually Matter?mentioning
confidence: 99%
“…Following substantial training in localizing a predictable target feature, phenotypically similar attentional biases can be observed without the use of explicit reward feedback (e.g., Kyllingsbaek et al, 2001, 2014; Qu, Hillyard, & Ding, in press; Shiffrin & Schneider, 1977). The training required to observe such attentional biases typically spans several thousand trials over multiple days, much longer than the brief single-session learning that is sufficient to generate value-driven attentional biases following rewarded training.…”
mentioning
confidence: 94%